2022
DOI: 10.1186/s40634-022-00501-y
|View full text |Cite
|
Sign up to set email alerts
|

Developing an experimental model of early knee osteoarthritis after medial meniscus posterior root release: an in vivo study

Abstract: Purpose To develop a predictable and reproducible model of knee osteoarthritis after medial meniscus posterior root release. Methods Posteromedial meniscal root tears were created in 12 White New Zealand rabbit knees. The contralateral limbs were used as healthy controls. The animals were euthanized at 16 weeks postoperatively; tissue samples of femoral and tibial articular cartilage were collected and processed for macro and microscopic analyses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Surgical destabilization of the meniscus root was conducted according to the previously described model. 18 The animals were euthanized at 16 weeks postoperatively; tissue samples of femoral and tibial articular cartilage were collected and processed for macro- and microscopic assessment to detect signs of early OA. The follow-up was set at 16 weeks as we considered this would be a proper timing to examine development of all relevant hallmark changes that are found in human OA, and based on previously published studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical destabilization of the meniscus root was conducted according to the previously described model. 18 The animals were euthanized at 16 weeks postoperatively; tissue samples of femoral and tibial articular cartilage were collected and processed for macro- and microscopic assessment to detect signs of early OA. The follow-up was set at 16 weeks as we considered this would be a proper timing to examine development of all relevant hallmark changes that are found in human OA, and based on previously published studies.…”
Section: Methodsmentioning
confidence: 99%
“…Large animal models remain a cornerstone to validate, improve, and aid early diagnosis of OA, providing a potential means to detect pathology at an earlier stage than is currently possible and to ascertain optimal future outcomes. 7,18,27,31,47 Rabbits are the most commonly used animal models, especially for knee OA. Over the past decades, multiple surgically induced instability models of OA in a rabbit have been reported to assess the therapeutic efficacy of compounds targeted for OA treatment because the procedure induces cartilage lesions similar to those observed in humans with OA.…”
mentioning
confidence: 99%
“…Regardless, MMPR repair does not completely prevent the progression of osteoarthritis and medial joint space (MJS) narrowing [2, 8, 14]. While many similar studies have reported on postoperative MM extrusion (MME) progression [19, 23, 29], a previous study reported that MMPR repair slowed the progression of osteoarthritis compared with conservative treatment or meniscectomy in a rabbit model [3]. Factors such as age, weight, quadriceps muscle strength, healing status of the repaired posterior roots and time from symptom onset to surgery have been reported to influence the progression of MJS, MME and osteoarthritis in the postoperative period after MMPR repair [7, 11, 24].…”
Section: Introductionmentioning
confidence: 99%